The way home. Season one [videorecording (DVD)] - Clarke, Alexandra; Harvey, Grant, 1966-; Bailey, Norma, 1949-; Mukerji, Nimisha; Sarif, Shamim; Calvert, John; Leigh, Chyler, 1982-; Williams, Evan (Actor); MacDowell, Andie; Laflamme-Snow, Sadie; Hook, Alex (Actor) (Hallmark, 2023)
A family drama following the lives of three generations of women Kat Landry, her 15-year-old daughter Alice, and Kat's mother Del. As the three generations of women slowly work on finding their footing as a family, they embark on an enlightening and surprising journey none of them could have imagined as they learn how to find their way back to each other.